A modern state of deer farming in Tuva - Biche-ool, Svetlana M.; Samdan, Ayana A. (The New Research of Tuva, 2012)
Article analyzes social, economic and ethnocultural situation in the communities of reindeer herders in Tuva, particularly, in Todzha district. Analysis is based on materials of statistics, archives and results of polls held during the period of 2007-2011.
Keywords: reindeer herders; transformation; indigenous small ethnic communities of Russia; deer farm